History of Bank of Japan's more than two decades of unconventional monetary easing with special emphasis on the frameworks pursued in the last 10 years - Pawel Kowalewski; Sayuri Shirai (Asian Development Bank Institute (ADBI), 2023)
Low inflation hit the Japanese economy shortly after the burst of the bubble in stocks and real estate in 1991 and has haunted the domestic economy ever since. The bubbles were partly attributable to prolonged monetary easing in the second half of 1980s, which was conducted to increase domestic demand and mitigate the recession induced by the appreciation of the Japanese yen. Furthermore, the country was adversely affected by US pressure to reduce trade deficits and resolve the prolonged trade dispute. In the early 1990s, Japan faced sluggish economic growth and low inflation, as well as severe structural financial and corporate sector balance sheet problems. Reflecting global trends regarding providing central banks with operational independence and the lessons learnt from Japan's bubble experience, meanwhile, the Bank of Japan (BOJ) was granted independence under the new 1997 Bank of Japan Act. Japan's economic problems starting from the 1980s also coincided with the period when the global Great Moderation was only it its early stages. The newly independent BOJ, in order not to put its credibility at risk, opted for cautiousness, which proved to be excessive. Not only was there a reversal in the August 2000 rate increase, but the BOJ also launched an unprecedented monetary experiment in 2001 called Quantitative Easing Policy. Moving the main operational target from short-term interest rates to current account balances at the BOJ and supplying sufficient liquidity beyond the required reserves was a milestone in the history of central banking. This shift was accompanied by subsequent novel monetary easing policies that were pursued over the last 20 years. Ever since, the BOJ has become not only a pioneer in pursuing unconventional monetary policies, but also a reference point for other central banks. At this stage, it is difficult to judge the effectiveness and efficiency of the BOJ's policy tools, as achievement of inflation beyond the 2% price stability target since last year is clouded by doubts regarding its sustainability. This paper provides a detailed description of the BOJ's policy, especially under Haruhiko Kuroda's 10-year governorship.
Keywords: E31; E52; E58; 330; monetary policy; yield curve control; quantitative and qualitative monetary easing; negative interest rate policy; the Bank of Japan; central bank independence; inflation targeting